Technology and Language Revitalization in Indonesia: A Literature Review of Digital Tools for Preserving Endangered Languages - Meida Rabia Sihite; Berlin Sibarani (International Journal of Educational Research Excellence (IJERE), 2024)
This systematic literature review examines specific digital tools such as mobile apps, online dictionaries, and social media platforms, evaluating their implementation and effectiveness in preserving endangered languages in Indonesia. Drawing from an analysis of ten scholarly publications spanning 2019 to 2023, key tools identified include the Android-based Lampung dictionary, "Nusantara in Your Hand" for Javanese and Madurese, and the Muyu-Indonesian-English Dictionary App. These tools engage communities through initiatives like the Balinese Language Digital Dictionary and BASAbali Wiki, utilizing platforms such as WhatsApp, Facebook, and YouTube for cultural preservation. Implementation strategies encompass a variety of mediums: mobile apps tailored for Lampung, Javanese, and Madurese speakers; comprehensive online platforms like the Balinese Language Digital Dictionary and BASAbali Wiki; interactive resources such as LearnJavaneseOnline.com; and dynamic social media engagement on WhatsApp, Facebook, Twitter, and YouTube. Utilizing modern technology, these tools document, teach, and sustain regional languages, enhancing accessibility and fostering community engagement. Their effectiveness lies in promoting community involvement, integrating into educational frameworks, and gaining support from governments and local communities, thus playing a crucial role in safeguarding Indonesia's linguistic heritage and cultural identity. In conclusion, digital tools present significant progress in preserving Indonesia's linguistic diversity, requiring strategies that address socio-cultural and technical challenges, prioritize community involvement, foster collaboration across sectors, improve digital infrastructure, and promote sustainable practices to ensure long-term success in language revitalization efforts.